"How does Buddhism help build Peace and Happiness in Cambodia thought, local ritual ceremonies, lifestyle, beliefs and tradition?" - Vy Sovechea, Venerable (วารสารวิชาการพระพุทธศาสนาเขตลุ่มน้ำโขง, 2018)
Buddhism was founded well over two thousand years ago in the 5th or 6th century BCE. Its ideas and practices are still evident in societies throughout the world today. Buddhism is the world's fourth largest religion, with about 350 million living adherents. Besides impacting those who study and practice Buddhism as their primary religion, Buddhism shapes modern philosophical outlooks, psychological conditions and political landscapes.             According to the Constitution of the Kingdom of Cambodia in article 42 states that "Buddhism shall be a state religion." 95 percent of Cambodians are Buddhists. In the present day, there are 70,853 monks among 15 million Cambodian people and 4,984 monasteries throughout the whole country.             In the year 238 B.C Emperor Asoka King sent two learned Bhikkhus, namely Sona Thera and Utara Thera, to propagate Buddhism in Suwanaphumi or Southeast Asia in the present time.             Cambodian ways of life have been connected to what the Buddha taught more than 2558 years ago. Buddhist monks and monasteries have played key roles in Cambodian society from generation to generation. Here we may know how Buddhism Influences Cambodian ways of life.              Impact of Buddhism to Cambodian Culture             Today Buddhism remains an influential force in Cambodia religion and in everyday life, but it is still rebuilding from the loss of so many leaders and teachers during the Khmer Rouge period. Moreover, in the countryside, Buddhist practice often embraces a synergetic blend of animism and indigenous spirit worship. Over the years, Buddhism has played a central role in Cambodian Society, serving as a blueprint for everyday life, a moral structure, a guide for family life, a basis for national holidays and cultural events, and a foundation for social policy.             The Khmer Rouge believed they could kill Buddhism. They tried to stamp it out, but Buddhism cannot die. Buddhism lives in Cambodian life, language and love for ancestors. Most of all, Buddhism lives deeply in Cambodian hearts. So, the Buddhist way of life and Cambodian culture are inseparable.